IMPLEMENTASI KOMUNIKASI VERBAL PENGURUS LEMBAGA DAKWAH KAMPUS UIN JAKARTA DALAM MENINGKATKAN UKHUWAH ISLAMIYAH - Akmal Dinullah; Nasichah Nasichah; Angel Cahya Raudhatul Jannah; Syifa Anivitariany Aqilah (Cross-border, 2023)
This journal reviews the Implementation of Verbal Communication from UIN Jakarta Campus Dakwah Management in Improving Ukhuwah Islamiyah. This study aims to describe or describe verbal communication between administrators of campus da'wah institutions within the UIN Jakarta environment that can increase ukhuwah Islamiyah which is an increase in solidarity and brotherhood in Campus Da'wah Institutions. This research method uses quantitative research using the questionnaire method or distributing research surveys to institutional administrators. campus da'wah at UIN Jakarta. As for the results of the research that the research that has been researched uses questionnaires to administrators of campus da'wah institutions at UIN Jakarta using verbal communication to show effectiveness where the effectiveness of verbal communication to administrators of campus da'wah institutions can increase ukhuwah Islamiyah by using polite language, active listening, and attention or empathy, in addition to that the administrators of the campus da'wah institution at UIN Jakarta to increase their Islamic ukhuwah they organize discussion forums, public lectures, Islamic studies, and social activities, for this ukhuwah Islamiyah at the Campus Da'wah Institute at UIN Jakarta can strengthen social bonds between them with verbal communication.